Sentinel lymph node biopsy with/without axillary dissection in clinically node-positive breast cancer after neoadjuvant chemotherapy - Cabioglu, Neslihan; Karanlik, Hasan; Gulcelik, Mehmet Ali; Ilgun, Serkan; Igci, Abdullah; Uras, Cihan; Cakmak, Guldeniz Karadeniz; Ugurlu, Umit; Muslumanoglu, Mahmut; Kocer, Havva Belma; Trabulus, Didem Can; Dag, Ahmet; et al. (SPRINGER, 2022)
23rd Annual Meeting of the American-Society-of-Breast-Surgeons, Las Vegas, NV, APR 06-10, 2022